Effect of pellet from total mixed ration on growth performance, blood metabolomics, carcass and meat characteristics of Bangladeshi garole sheep - Islam, R; Redoy, MRA; Shuvo, AAS; Sarker, MAH; Akbar, MA; Al-Mamun, M (Progressive Agriculture, 2017)
Six indigenous Bangladeshi Garole sheep (Ovis aries) (BW: 8±0.5 kg; Age: 1yr) were divided into two groups using a randomized block design to investigate the effect of total mixed ration (TMR) pellet feeding on growth parameter, blood metabolomics, carcass and meat characteristics. Control diet was composed of road side grass, rice straw, wheat bran, mustard oil cake, molasses, common salt which considered as loose total mixed ration (L-TMR) and treatment diet was pelleted form of L-TMR (P-TMR).In both the dietary treatments the animals were fed at 1.5 times of maintenance energy and protein requirement. P-TMR revealed a positive impact (p < 0.05) on live weight gain and feed conversion ratio than L-TMR. Total digestible nutrients (TDN) and digestible crude fibre (DCF) was significantly higher (p < 0.05) in P-TMR group whereas there was no significant difference (p < 0.05) in other digestible nutrients as well as plasma metabolites like plasma glucose, triglyceride, total cholesterol, HDL-cholesterol and LDL- cholesterol concentration between two dietary group. Dressing percentage and eye muscle area was significantly higher (p < 0.05) in P-TMR group but no significant difference was found between dietary treatments in term of disposition of body fat, proximate composition of mutton, all the sensory parameters except tenderness and overall acceptability. So, it could be concluded that, the P-TMR might be fed to sheep for better growth performance and higher meat production rather than production of functional mutton. Progressive Agriculture 28 (3): 222-229, 2017